SISTEM INFORMASI MANAJEMEN MASJID AT- TAUBAH DESA UMA BERINGIN BERBASIS WEB - Ayunda, Evi; Rodianto, Rodianto (Smart Education, 2025)
Abstract: In the 4.0 era, information technology is developing rapidly, bringing many changes and conveniences in various aspects (Zamzami et al., 2024). Almost all aspects of life involve the development of information technology, causing the majority of organizational entity management decisions to be influenced by information technology (Anggraini, 2021). One aspect of life that has not utilized technology optimally is the mosque. Information technology is developing rapidly so it can continue to be used to help complete various jobs (Akbar et al., 2022). Technological developments continue to give rise to innovations, one of which is web-based systems (Rezki et al., 2024). This innovation is a solution that can help overcome the administrative problems of the Taubah mosque. By developing an information system used for management so that mosque management activities can be carried out effectively and efficiently (Rezky et al., 2021). In conducting this research, researchers used a research method using software design using the waterfall method. The results obtained in this research are that the website that was built can make it easier for users to access the information provided by the mosque management, making it easier for the public to know what activities are provided by the mosque. Keyword: System;Information System;Website. Abstrak: Pada era 4.0 teknologi informasi berkembang pesat yang membawa banyak perubahan dan kemudahan dalam berbagai aspek (Zamzami et al., 2024). Hampir seluruh aspek kehidupan yang melibatkan perkembangan teknologi informasi sehingga menyebabkan sebagian besar keputusan manajemen entitas organisasi dipengaruhi oleh teknologi informasi (Anggraini, 2021). Salah satu aspek kehidupan yang belum maksimal pemanfaatan teknologi adalah masjid. Teknologi informasi yang berkembang pesat sehingga dapat terus dimanfaatkan untuk membantu menyelesaikan berbagai pekerjaan (Akbar et al., 2022). Perkembangan teknologi terus melahirkan inovasi salah satunya sistem berbasis web (Rezki et al., 2024). Inovasi tersebut menjadi solusi yang dapat membantu mengatasi permasalahan administrasi dari masjid Taubah. Dengan pengembangan sistem informasi yang digunakan untuk memamanajemen sehingga kegiatan manajemen kepengurusan masjid dapat dilakukan secara efektif dan efisien (Rezky et al., 2021). Dalam melakukan penelitian ini peneliti menggunakan metode penelitian menggunakan perancangan perangkat lunak dengan meenggunakan metode waterfall. Adapun hasil yang didapatkan pada penelitian ini adalah website yang dibangun dapat memudahkan pihak pengguna dalam mengakses informasi yang diberikan oleh pengelola masjid sehingga memudahkan masyarakat dalam mengetahui kegiatan apa saja yang diberikan oleh masjid. Kata kunci: Sistem,;Sistem Informasi;Website.